Computation of temperature distributions on uniform and non-uniform lattice sizes using mesoscopic lattice boltzmann method / D. Arumuga Perumal ... [et al.] - D. Arumuga Perumal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
This work is concerned with the mesoscopic lattice Boltzmann computation of heat conduction problems on uniform and non-uniform lattice sizes. It also focuses to solve heat conduction problems in one- and two-dimensional Cartesian geometries. It is known that, the lattice Boltzmann method is a relatively new method and application to heat conduction problems is scarce. In the present work, heat transfer formulations of lattice Boltzmann method to solve heat transfer problems are presented and implementation of non-uniform lattices is described. To show the accuracy and stability of the present lattice Boltzmann method, number of iterations and CPU time are reported. In order to study the effect of lattice structure, uniform and non-uniform lattice sizes are performed. To lend credibility to the lattice Boltzmann results they are further compared with those obtained from a finite difference method. It is concluded that the present study in heat conduction produces results that are in excellent contribution of lattice Boltzmann method in the area of computational fluid dynamics.